A Loss of Judgment: The Dismissal of the Judicial Conscience in Recent Christian Ethics. Issue 3 (September 2017) - Morgan, Jeffrey
Abstract: Christian ethicists have neglected conscience, understood as an individual's moral self‐awareness before a locus of accountability and judgment, over the last few decades. The aim of this essay is to suggest how this neglect came about. I draw on the work of Paul Lehmann and Oliver O'Donovan to illustrate how ethicists in the twentieth century became suspicious of conscience because of its association with the alleged ahistorical individualism of Immanuel Kant's work. I argue that a social‐historicist conception of conscience, such as H. Richard Niebuhr offered, attempts to save conscience from this suspicion. Ironically, however, Stanley Hauerwas's development of Niebuhr's historicist, communitarian approach to conscience, appears to have led to a dismissal of conscience. I conclude with a brief comment about what this dismissal has cost contemporary Christian ethics, namely the Christian tradition's basic commitment to the singularity of an individual's accountability before God.